Indirect Self-Destructiveness in Women who Experience Domestic Violence - Tsirigotis, Konstantinos (Psychiatr Q, 2018)
Lives of people experiencing domestic or/and intimate partner violence abound in many unpleasant events and physical and psychological suffering, which affects their psychosocial functioning. The aim of this study was to explore indirect self-destructiveness as a generalised behavioural tendency and its manifestations in women experiencing domestic violence. The “Chronic Self-Destructiveness Scale” (CS-DS) was used to study two groups of women: 52 women aged 30–65 years (mean age: 40.15) using assistance of the Crisis Intervention Centre due to experienced domestic violence (V group) and 150 well-matched women not experiencing domestic violence (NV group). Women suffering domestic violence (V) obtained significantly higher scores than women not experiencing domestic violence (NV) for both the general index and a majority of CS-DS subscales; it was only for the A1 (Transgression and Risk) subscale that they achieved somewhat lower scores. Correlation coefficients between particular CS-DS subscales in the V group were higher than in the NV group; there were also certain differences in coefficients between the groups. Subscale factor analysis results were different too: only one factor was isolated in the V group while two were distinguished in the NV group. It can be inferred from the results that the intensity of indirect self-destructiveness as a generalised behavioural tendency as well as of most its categories was higher in women experiencing domestic violence. Tendencies and categories of indirectly self-destructive behaviours in women suffering domestic violence were more closely connected with one another, and the internal coherence of indirect self-destructiveness in those women might also be higher.